Simultaneous Quantitative Determination of Ciprofloxacin and Hydrocortisone by H-Point Standard Addition Method - Khalil Mahmood, Ali; Takleef Dheyab Sallal,; Luaibi , Hasan Mohammed; Al-Janabi, Khalid Waleed S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Ciprofloxacin (Cip) and hydrocortisone (Hyd) were simultaneously measured as hydrochloride and sodium succinate, respectively, using the H-point standard addition method (HPSAM). The approach can precisely identify Cip in the presence of Hyd with various analyte-to-interference ratios (5:5, 5:10, 10:5, 10:10) µg.mL-1, in mixed samples containing (1-5µg.ml-1) of Cip, at the wavelengths of (236 and 257) nm. In the same way, Hyd was analyzed in the presence of Cip in different analytes with an interference ratio of (5:5, 5:10, 10:5, 10:10) µg.mL-1, in mixed samples containing (1-5 µg.mL-1) of Hyd, at wavelengths of (266 and 278) nm. The satisfactory results show good reproducibility of the developed method (RSD equals 0.9735-1.6825 and 0.9692-1.7671 for Cip and Hyd, respectively). The results also show that the excipients had no influence on the assaying of the above drugs (Recovery, 98.87–101.73). The recommended technique has successfully been used to determine the Cip and Hyd in pharmaceutical composites simultaneously with an RSD range of (0.972 to 1.671) and (0.898 to 1.820) for Cip and Hyd, respectively.